Lipidomics of familial longevity. Issue 3 (2nd April 2013) - Gonzalez‐Covarrubias, Vanessa; Beekman, Marian; Uh, Hae‐Won; Dane, Adrie; Troost, Jorne; Paliukhovich, Iryna; van der Kloet, Frans M.; Houwing‐Duistermaat, Jeanine; Vreeken, Rob J.; Hankemeier, Thomas; Slagboom, Eline P.
Summary: Middle‐aged offspring of nonagenarians, as compared to their spouses (controls), show a favorable lipid metabolism marked by larger LDL particle size in men and lower total triglyceride levels in women. To investigate which specific lipids associate with familial longevity, we explore the plasma lipidome by measuring 128 lipid species using liquid chromatography coupled to mass spectrometry in 1526 offspring of nonagenarians (59 years ± 6.6) and 675 (59 years ± 7.4) controls from the Leiden Longevity Study. In men, no significant differences were observed between offspring and controls. In women, however, 19 lipid species associated with familial longevity. Female offspring showed higher levels of ether phosphocholine (PC) and sphingomyelin (SM) species (3.5–8.7%) and lower levels of phosphoethanolamine PE (38:6) and long‐chain triglycerides (TG) (9.4–12.4%). The association with familial longevity of two ether PC and four SM species was independent of total triglyceride levels. In addition, the longevity‐associated lipid profile was characterized by a higher ratio of monounsaturated (MUFA) over polyunsaturated (PUFA) lipid species, suggesting that female offspring have a plasma lipidome less prone to oxidative stress. Ether PC and SM species were identified as novel longevity markers in females, independent of total triglycerides levels. Several longevity‐associated lipids correlated with a lower risk of hypertension and diabetes in the Leiden Longevity Study cohort. This sex‐specific lipid signature marks familial longevity and may suggest a plasma lipidome with a better antioxidant capacity, lower lipid peroxidation and inflammatory precursors, and an efficient beta‐oxidation function.